2015
DOI: 10.3390/ma8063238
|View full text |Cite
|
Sign up to set email alerts
|

Microleakage of Different Self-Adhesive Materials for Lithium Disilicate CAD/CAM Crowns

Abstract: Objectives: To evaluate the microleakage and marginal gap of various luting materials after cementing ceramic crowns. Methods: Cervical margins of human molars were designed as circular chamfers. Cementation of full-contour ceramic crowns was conducted with zinc-phosphate cement (Harvard cement), resin cement (Panavia F 2.0) and self-adhesive resin cements (RelyX Unicem, BifixSE, MaxCem Elite, PermaCem2.0, G-Cem). Aging of specimens was performed in artificial saliva, at 37 °C for four weeks and thermocycling.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…The results obtained in the present study as zero score for marginal adaptation were attributed to the butt-joint incisal configuration and preservation of a peripheral enamel layer around all margins, also, this design established an easy path of insertion of the laminate during bonding [30]. Najim et al [31] found that the CAD/CAM veneers with butt joint incisal reduction produced the most accurate margins while the least favorable combination was the pressable ceramic veneers with overlapped incisal reduction.…”
Section: Marginal Adaptation Resultssupporting
confidence: 63%
“…The results obtained in the present study as zero score for marginal adaptation were attributed to the butt-joint incisal configuration and preservation of a peripheral enamel layer around all margins, also, this design established an easy path of insertion of the laminate during bonding [30]. Najim et al [31] found that the CAD/CAM veneers with butt joint incisal reduction produced the most accurate margins while the least favorable combination was the pressable ceramic veneers with overlapped incisal reduction.…”
Section: Marginal Adaptation Resultssupporting
confidence: 63%